Cylinder Lottery. - Shasha, Dennis (Communications of the ACM, 2025)
The author presents a probabilistic game involving cylinders, each containing $100, in which a contestant aims to collect all the money in the fewest possible draws despite constraints like cylinder reshuffling, optional "cleanings" (removal of empty cylinders), and "refillings" (returning some empty cylinders). It presents solutions for scenarios with varying numbers of cylinders, cleanings, and refillings, demonstrating how strategic timing of cleanings can drastically reduce the expected number of draws, especially as the game complexity increases. The article suggests that dynamic programming can optimize strategies when balancing cleanings and refillings for minimal expected draws.